Restorative Justice pada Perkara Lingkungan Hidup dalam Perspektif Penuntutan Jaksa - Susanti, Huni; Nufninu, Misi (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study explores the potential application of restorative justice in environmental crime cases in Indonesia from the perspective of public prosecutors. While the conventional litigation process in environmental law is often lengthy, costly, and ineffective at ensuring ecological recovery, restorative justice offers an alternative that emphasizes efficiency, participation, and direct environmental rehabilitation. Employing a qualitative approach with grounded theory methodology, data were collected through in-depth interviews with prosecutors, supported by document analysis and constant comparative coding. The findings reveal that most prosecutors view restorative justice positively as a mechanism to accelerate case resolution and enhance ecological restoration. However, normative and institutional barriers, as well as the risks of misuse, remain critical challenges. Axial and selective coding led to the construction of a substantive theory that highlights the central role of prosecutors in navigating regulatory gaps and facilitating multi-actor commitments for ecological justice. This research contributes conceptually by integrating restorative justice with the unique characteristics of environmental law and practically by providing recommendations for policymakers to design regulations and technical guidelines that support its consistent and transparent implementation.